Prevalence, Magnitude, and Methods of Weight Cutting Used by World Class Powerlifters. Issue 4 (9th April 2022) - Kwan, Kedric; Helms, Eric
Abstract: Kwan, K and Helms, E. Prevalence, magnitude, and methods of weight cutting used by world class powerlifters. J Strength Cond Res 36(4): 998–1002, 2022—Powerlifters compete in the squat, bench press, and deadlift, with winners determined by the highest 3-lift total in each weight class. As a weight class–based sport, athletes often compete in classes lower than their habitual weight, using various strategies to make weight. This study's purpose was to examine weight cutting prevalence, magnitude, and methods among 42 male and 22 female powerlifters (25 ± 8 years old; 4 ± 2.2 years of competitive experience) competing at the 2018 International Powerlifting Federation classic world championship. The lifters, 83% of whom cut weight losing an average 2.9 ± 4.3% of body mass, completed a previously validated weight cutting questionnaire. The most frequently used weight cutting methods were gradual dieting (42.18%, 31.25%), fluid restriction after fluid loading (32.8%, 34.4%), restricting fluid ingestion without fluid loading (23.4%, 9.4%), fasting (15.6%, 18.7%), increased activity (9.4%, 24.4%), laxatives (9.4%, 18.7%), sauna (7.8%, 6.3%), diuretics (7.8%, 6.3%), skipping meals (4.7%, 21.9%), and wearing rubber suits (1.6%, 2.6%). Most lifters experienced negative changes in psychological state, with only 9% reporting never experiencing any negative effect on psychological state across the 5 states measured. Lifters reported experiencing fatigue (15.6%, 45.3%), anger (3.2%, 26.6%), feelings of isolation (4.7%, 12.5%), and anxiety (14.1%, 35.95%), and 11 of the 12 lifters who reported a perceived decrement in training performance performed weight cutting. Both weight cutting methods and negative psychological changes experienced were reported as always, sometimes. Therefore, it is vital to provide specific recommendations based on scientific research to improve the efficacy and safety of making weight while minimizing performance decrements.